Evaluasi Advokasi Penyelesaian Konflik Sengketa Tanah di Kabupaten Banggai, Sulawesi Tengah - Adriany Badrah (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2011)
This research aims to determine the extent to which advocacy is conducted by Front Rakyat Advokasi Sawit (FRAS) for the handling of conflict in Central Sulawesi land disputes between famers Toili and PT Kurnia Luwuk Sejati (PT KLS). The background of this research is about the conflict of land disputes between farming communities Toili with PT KLS in Banggai regency of Central Sulawesi province. This study uses the method of evaluation that is part of the decision making process, namely to compare an event, activity has been determined. This study uses qualitative analysis and data types. Qualitative research aims to describe and analyze problems that become the object of this study as an evaluation of the advocacy process, so this study can give an idea about advocacy in conflict resolution of land disputes and the factors surrounding the advocacy process to determine the success or failure of advocacy efforts related to resolving conflicts and land disputes Toili farmers PT KLS.